2010
DOI: 10.1159/000315435
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Attenuates Iodine Contrast Agent-Induced Nephropathy in 5/6-Nephrectomized Rats

Abstract: Aims: In the present study we tested the efficacy of N-acetylcysteine (NAC) to minimize nephrotoxic effects of iodine contrast agents in intact rats as well as in 5/6-nephrectomized (5/6-Nx) rats. Methods: Rats were allocated to a group of intact rats (n = 42) and a group of 5/6-Nx rats (n = 42). After 1 month of recovery from surgery, 5/6-Nx rats and intact (sham-operated) animals received either 6 ml/kg body weight (b.w.) meglumine ioxithalamate (Telebrix 350) or 6 ml/kg b.w. iohexol (Omnipaque 350) intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 93 publications
0
8
0
2
Order By: Relevance
“…Therefore, various blood flow-increasing agents were clinically tested to prevent CIN; however, most of these have been reported to be ineffective [2]. In the experimental and/or clinical studies, caffeic acid phenyl ester (CAPE), N-acetylcysteine (NAC) and ascorbic acid have been reported to have positive effects in preventing CIN [7,11,12,13,14]. For this purpose, oxidative stress, rather than decrease in renal blood flow, is considered to play an important role in CIN development [2].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, various blood flow-increasing agents were clinically tested to prevent CIN; however, most of these have been reported to be ineffective [2]. In the experimental and/or clinical studies, caffeic acid phenyl ester (CAPE), N-acetylcysteine (NAC) and ascorbic acid have been reported to have positive effects in preventing CIN [7,11,12,13,14]. For this purpose, oxidative stress, rather than decrease in renal blood flow, is considered to play an important role in CIN development [2].…”
Section: Discussionmentioning
confidence: 99%
“…On day 0, 5 ⁄ 6 NX was carried out under anaesthesia (tiletamine + zolazepam; Virbac SA, Carros Cedex, France; 8 mg ⁄ kg; and xylasine, Spofa, Czech Republic; 4 mg ⁄ kg intramuscularly), as described previously. 3,7,8,13,17,18,20,43,44 Briefly, an abdominal midline incision was carried out to expose the kidneys. The right kidney and both poles of the left kidney were removed surgically in order to remove 5 ⁄ 6 of renal parenchyma, as estimated by kidney weight.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…This approach was previously validated in our laboratory and is regularly used in our studies. 27,29,40,43,44 Series 2: Effects of RAS-dependent and RAS-independent antihypertensive therapy on plasma and kidney AngII levels, cardiac hypertrophy, renal glomerular damage and kidney tubulointerstitial injury Animals were divided into the following experimental groups and were exposed to the same experimental protocol as in series 1:…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…To evaluate the renoprotective effects of various compounds, the experimental AKI rat model is useful and the results can be extrapolated to clinical AKI (4,31,36). Few compounds have been used in clinical trials and found to have therapeutic value.…”
mentioning
confidence: 99%